2021
DOI: 10.1177/21533687211015287
|View full text |Cite
|
Sign up to set email alerts
|

Structural Racism and Criminal Violence: An Analysis of State-Level Variation in Homicide

Abstract: We advance a structural racism approach to understanding the variation in homicide across the U.S. states. We conceptualize structural racism by juxtaposing the conditions for Blacks with those for Whites across multiple domains. We also include two ideological beliefs, racial resentments and Whites perceptions that their racialized social status is threatened by minority gains. The results show that higher Black homicide rates are associated with greater exposure to structural racism and that states with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…It is thus no coincidence that these structurally imposed economic landscapes promote high-risk behaviours aimed at capturing key resources that can be attained by individuals from privileged backgrounds through safe, non-illicit means (Wilson & Daly, 1997 ). We suggest that these results, in line with arguments from Unnever et al ( 2021 ), provide compelling evidence to expand strategies for reducing homicide rates by dismantling structures of systemic racism that generate and concentrate sustained poverty and economic inequality.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is thus no coincidence that these structurally imposed economic landscapes promote high-risk behaviours aimed at capturing key resources that can be attained by individuals from privileged backgrounds through safe, non-illicit means (Wilson & Daly, 1997 ). We suggest that these results, in line with arguments from Unnever et al ( 2021 ), provide compelling evidence to expand strategies for reducing homicide rates by dismantling structures of systemic racism that generate and concentrate sustained poverty and economic inequality.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, this framework suggests that homicide rates disproportionately impact non-white communities owing to a long history of systemic racism towards racial and ethnic minority groups – especially Black communities (Schober et al, 2021 ) – that restrict individuals’ access to resources and opportunities (Daly, 2016 ; Yearby, 2018 ). Numerous studies have shown that across the US, in both contemporary and historic times, poverty and economic inequality are concentrated in minority communities due to ongoing legacies of systemic disadvantage (Bonilla-Silva, 2015 ; Daly, 2016 ; Schober et al, 2021 ; Unnever et al, 2021 ). It is thus no coincidence that these structurally imposed economic landscapes promote high-risk behaviours aimed at capturing key resources that can be attained by individuals from privileged backgrounds through safe, non-illicit means (Wilson & Daly, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in this tradition focuses on historical continuities in processes of racial domination like colonialization (Hawkins, 2011), racially restrictive residential process (Bass, 2001), and the general demoralization of people of color (Keahiolalo-Karasuda, 2010;Tatum, 2017). Closely related are theories of structural or systemic racism (Sewell, 2020;Unnever et al, 2021). These historically contiguous processes of structural racial control could help explain why the effect of jail on employment would be moderated by local racial composition.…”
Section: Crimrxivmentioning
confidence: 99%
“…The third aim of this paper was to test the utility of the novel city-level structural racism measure by assessing its relationship with Black-White racial disparities in firearm homicide at the city level. We chose firearm homicide because there is an abundance of evidence that structural racism is related to racial disparities in this outcome, with at least 11 papers documenting this relationship: three at the neighborhood level [ 17 19 ], one at the city level [ 20 ], one at the county level [ 7 ], one at the metropolitan statistical area level [ 21 ], and five at the state level [ 13 , 14 , 22 – 24 ]. In particular, we compared the magnitude of the relationship between changes in the structural racism measure and changes in the ratio of Black to White firearm homicide rates observed in this study with that reported in the one previous study that examined this relationship at the city level [ 20 ].…”
Section: Introductionmentioning
confidence: 99%